Students' Difficulty In Learning Tenses - Hasibuan, Agus Salim; Hutagalung, Rahmad Rizki; Lestari Pane, Tiara Indah; Fadillah, Wisnu; Lubis, Yani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
English is an international language used by many foreign countries. In Indonesia, there is very little interest in the use of English because many people, especially students, are reluctant to learn English. To be able to learn English, you need to know the basics to make it easier to understand the lesson in question. Tenses are an example of the basic forms of learning in English. Through tenses, we can differentiate sentence forms by adjusting the time specified. The use of tenses also adapts to the time when used in conversation. By understanding tenses as the basis for mastering English, it will make it easier to communicate with foreign citizens, make it easier to get information related to education in English so that the insight we gain does not only come from our own country's language but we have insight from abroad. Very few people really understand mastery in learning tenses. This is because the delivery of the material is less interesting, so students are also reluctant to express their interest in English. For this reason, we gathered several students to find out the extent of their understanding of tenses. Having a discussion will make your peers understand more about learning that is not understood in class. Through peers it is possible to gain more efficient understanding